An Overview of Artificial Intelligence (AI) Issues from the Perspective of Islamic Jurisprudence - Mustapha, Ariyanti; Senik@ Kamaruddin, Zuraidah; Che Haron, Sueraya (Online Journal of Research in Islamic Studies, 2025)
The advancement of artificial intelligence (AI) is significantly transforming the educational landscape, shifting pedagogical practices from traditional methods to technology-driven approaches. This evolution is in alignment with the objectives of maqāṣid al-sharī‘ah, particularly the preservation and enhancement of knowledge in the domains of science and technology. However, the integration of AI in education has also raised pressing ethical concerns, especially in relation to academic misconduct such as plagiarism and the decline of students’ critical and creative thinking abilities. This article adopts a qualitative and empirical methodology, drawing on data from selected academic journals related to AI in education and society, published between 2019 and 2024. Additionally, references from classical and contemporary Islamic scholarly works, as well as survey data collected from students are utilized to explore the dual impact of AI in educational fields. While AI presents substantial potential as an effective and supportive learning tool, this study highlights the importance of mitigating its ethical misuse among students. The integration of Islamic ethical principles is proposed as a critical measure for promoting responsible and values-based AI usage in academic contexts. To this end, the article proposed the TAQIT guideline, an acronym for Tabayyun (Verification), Akhlāq (Virtue Ethics), ‘Aql (Intellect), Amanah (Integrity), and Taqwā (God-Consciousness) as a holistic ethical framework that synthesizes divine law, moral principles, and social responsibility. This model aims to curb academic dishonesty and foster an ethical, spiritually grounded approach to learning in the age of AI.